Every Little Bit Counts: The Impact of High-Speed Internet on the Transition to College - Dettling, Lisa J.; Goodman, Sarena; Smith, Jonathan (The Review of Economics and Statistics, 2018)
This paper examines whether high-speed Internet affects students' college applications. Our analysis links the diffusion of residential broadband to the testing and application outcomes of millions of PSAT and SAT takers and reveals that students with broadband in their postal code perform better on the SAT and apply to a higher number and more expansive set of colleges. While the availability of broadband generally improved applications to college, the effects appear to be concentrated among high-SES students, suggesting that the new technology may have increased preexisting inequities.